Estudo de diretrizes termo-ambientais para o planejamento urbano da cidade de Corrente, Piauí, nordeste do Brasil. - Silva, Narciso Amaral da (2007)
Making use of a series of hourly-checked data, of temperature and relative air humidity, wind s speed and direction, measured simultaneously in three meteorological stations installed in the urban mesh of the Corrente-PI and in a INPE s standard station (for reference), located outside of the urban mesh, in which, besides the series of data already mentioned, also measured a series of solar radiation and accumulated precipitation during the year of 2006, objecting to evaluate the occupation s standard of the city s landscape and its inter-relations with the variable thermal-environmental measured, having reached the conclusion that it s soil occupation pattern is inadequate to the local climate, detecting an heat zone in the order of 5ºC, from which some guidelines were defined to allow a sustainable development.